2020
DOI: 10.5194/egusphere-egu2020-9869
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Are Collembola flying onto green roofs?

Abstract: <p><strong>Are Collembola flying onto green roofs?  </strong></p><p>With a worldwide urban population projected to reach 5 billion by 2030 (Véron, 2007), the roles and benefits of urban green spaces cannot be denied, like climate regulation by trees or water flow regulation (Gómez-Baggethun and Barton, 2013). If green spaces are among the new societal expectations of urban people, they also play a cruci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
2
7
1
1
Order By: Relevance
“…In this study, we find that most land snail species encountered are indeed well-documented greenhouse inhabitants (Table 2). A similar mechanism has been suggested for the dispersal of Collembola (springtails) onto green roofs via composting for roof soil enrichment [30]. If our findings are validated with further research, it could provide useful insight into the dynamics of how green roof ecosystems are created and change through time.…”
Section: Discussionsupporting
confidence: 75%
“…In this study, we find that most land snail species encountered are indeed well-documented greenhouse inhabitants (Table 2). A similar mechanism has been suggested for the dispersal of Collembola (springtails) onto green roofs via composting for roof soil enrichment [30]. If our findings are validated with further research, it could provide useful insight into the dynamics of how green roof ecosystems are created and change through time.…”
Section: Discussionsupporting
confidence: 75%
“…The factors that were found to enhance biodiversity were high vegetation cover ( Schindler, Griffith & Jones, 2011 ; Gonsalves, 2016 ), larger roof size ( Berthon, 2015 ), connectivity with other potential habitats ( Berthon, 2015 ; MacIvor, 2016 ; Blank et al, 2017 ; Ksiazek-Mikenas et al, 2018 ; Wang et al., 2017 ), greater vegetation complexity (i.e., height) ( Madre et al, 2013 ; Gonsalves, 2016 ), plant species diversity ( Gonsalves, 2016 ; Kratschmer, Kriechbaum & Pachinger, 2018 ; Ksiazek-Mikenas et al, 2018 ), and greater substrate depth ( Kratschmer, Kriechbaum & Pachinger, 2018 ), or substrate depths under 10 cm or over 15 cm ( Kyrö et al, 2018 ). On the other hand, the type of green roof, extensive or intensive, ( Joimel et al, 2018 ), roof age ( Schrader & Böning, 2006 ), and vegetation cover ( Rumble & Gange, 2013 ) did not affect soil microarthropod diversity in other studies. It was suggested that habitat heterogeneity may be an important factor in increasing these species’ diversity ( Rumble & Gange, 2013 ).…”
Section: Introductionmentioning
confidence: 73%
“…More specifically, to the best of our knowledge, only three related studies exist: Schrader and Böning, 2006;Rumble andGange, 2013 andJoimel et al, 2018 (Table 4). Given the fact that only a few studies have been performed on collembolan communities in Western Europe on green roofs, we will compare our results where possible with these studies (Schrader and Böning, 2006;Rumble and Gange, 2013;Joimel et al, 2018).…”
Section: Discussionmentioning
confidence: 99%